Normative data on audiovisual speech integration using sentence recognition and capacity measures. (2nd April 2016) - Altieri, Nicholas; Hudock, Daniel
Abstract: Objective : The ability to use visual speech cues and integrate them with auditory information is important, especially in noisy environments and for hearing-impaired (HI) listeners. Providing data on measures of integration skills that encompass accuracy and processing speed will benefit researchers and clinicians. Design : The study consisted of two experiments: First, accuracy scores were obtained using City University of New York (CUNY) sentences, and capacity measures that assessed reaction-time distributions were obtained from a monosyllabic word recognition task. Study sample : We report data on two measures of integration obtained from a sample comprised of 86 young and middle-age adult listeners: Results : To summarize our results, capacity showed a positive correlation with accuracy measures of audiovisual benefit obtained from sentence recognition. More relevant, factor analysis indicated that a single-factor model captured audiovisual speech integration better than models containing more factors. Capacity exhibited strong loadings on the factor, while the accuracy-based measures from sentence recognition exhibited weaker loadings. Conclusions : Results suggest that a listener's integration skills may be assessed optimally using a measure that incorporates both processing speed and accuracy.